The Optional Status of Albanian Language in Primary Education - Tofovikj Kjamilova, Marija; Tomevska Ilievska, Elizabeta; Sejdini, M. (Yıldız Technical University, Turkey, 2015)
Knowledge of the language of the broader environment presents an extraordinary benefit, and the process itself can start from the earliest school age. The research issues that are covered in this work are the didactic aspects of the implementation, organizational ordering, and coverage of Albanian Language as an elective subject in the nine-year primary education. Special emphasis is put on the manner and coverage of the realization of the elective subject Albanian Language in the nine-year primary education. This issue is studied from the aspect of examining the program foundations of the subject in question, the didactic qualities of the textbooks, and the opinions of the participants in the educational process. The research resulted in several conclusions that can positively influence the strengthening and development of the teaching of this specific subject. Generally, they come down to the existence of positive opinions from the participants of other ethnicities, the need for strengthening and reprogramming the textbooks, as well as the programs themselves. Such research provides possibilities for expansion and addition from the aspect of the organization and realization of Albanian Language as an elective subject in the nine-year primary education in those classes with other languages of instruction.
Keywords: multicultural education, teaching plans and programs, textbooks, elective subject, integrated teaching